Visual Customer Behavior Analysis Based on Customer Movements - Kröckel, Johannes; Bodendorf, Freimut (Proceedings of the 7th International Conference on Information Technology and Applications (ICITA 2011), 2011)
Today's retail stores are facing new challenges. While a few years ago competitive advantages could be achieved by well-stocked product portfolios and bargain prices both domains have been lost to internet shops. To preserve and improve customer retention in stationary retail environments sophisticated customer approaches such as customized services or optimized retail environments are crucial. Therefore, comprehensive knowledge of the customers has to be available. In order to gain this knowledge without using vague customer surveys or short-time observations an automated solution is desirable. An approach for capturing and processing customer movement data by using network cameras and algorithms from the field of computer vision is introduced. Two image processing methods are presented and evaluated. The extracted information is used for analyzing and visualizing customer behavior by the popular regions algorithm and Markov chains. The approach is exemplarily applied to a testing environment showing considerable differences in customer behavior for two settings.
WiSo2-Import:2015-10-02:587
Keywords: Customer Behavior Analysis; Customer Tracking; Markov Models; Regions of Interest